2020
DOI: 10.3174/ajnr.a6903
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 4D MR Angiography at 3T Compared with DSA for the Follow-up of Embolized Brain Dural Arteriovenous Fistula: A Dual-Center Study

Abstract: BACKGROUND AND PURPOSE: 4D contrast-enhanced MRA in the follow-up of treated dural arteriovenous fistulas has rarely been evaluated. Our aim was to evaluate its diagnostic performance at 3T in the follow-up of embolized dural arteriovenous fistulas using DSA as the standard of reference. MATERIALS AND METHODS: Patients treated for dural arteriovenous fistulas in 2 centers between 2008 and 2019 were included if they met the following criteria: 1) dural arteriovenous fistula embolization, and 2) follow-up imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“… 18 , 19 , 20 Temporal resolution and intracranial hemodynamics can be ascertained by DCE-MRA, for determining classifications related to venous drainage of DAVFs. 21 DCE-MRA can provide the added value of real time physio-pathological data regarding DAVF hemodynamics. Intracranial high-resolution VW-MRI can help to systematize the evaluation of DAVFs, rendering correct vascular descriptions.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 , 20 Temporal resolution and intracranial hemodynamics can be ascertained by DCE-MRA, for determining classifications related to venous drainage of DAVFs. 21 DCE-MRA can provide the added value of real time physio-pathological data regarding DAVF hemodynamics. Intracranial high-resolution VW-MRI can help to systematize the evaluation of DAVFs, rendering correct vascular descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRA can provide temporal resolution and identify intracranial hemodynamics and venous drainage, thus determining Borden or Cognard classifications. 38 , 39 , 40 Venous drainage patterns can predict the risk of ICH and NHND, such as vascular edema and cytotoxic edema. 28 , 32 , 41 , 42 The gold standard for clarifying the direction of DAVF venous drainage remains cerebral angiography based on selective catheter intubation.…”
Section: Advanced Mri For Davfsmentioning
confidence: 99%
“…Certain studies comparing DCE-MRA with DSA have demonstrated that DCE-MRA can diagnose DAVFs and identify the direction of venous drainage. 38 , 39 Therefore, DCE-MRA can be used as a preliminary diagnostic pre-surgical tool. 39 , 40 , 43 , 44 In terms of DAVF treatment, the individual needs of specific patients must be analyzed in detail.…”
Section: Advanced Mri For Davfsmentioning
confidence: 99%
“…Digital subtraction angiography (DSA) is regarded as the gold standard for measuring intracranial stenosis. However, DSA is an invasive modality and has the risk of ionizing radiation and the incidence of potential subsequent contrast-related complications ( 3 ). Therefore, non-invasive and accurate methods for the assessment of ICAS are gaining promise.…”
Section: Introductionmentioning
confidence: 99%